Bilateral agreement for academic years 2013/2014 Lifelong Learning Programme (Erasmus) between Universidade Lusíada de Lisboa and Sapienza - Università di Roma - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Lifelong Learning Programme / Erasmus. - Subject area: Law